Existential-Phenomenological Perspectives in Psychology 1989
DOI: 10.1007/978-1-4615-6989-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Research Methods

Abstract: Research methods are plans used in the pursuit of knowledge. They are outlines of investigative journeys, laying out previously developed paths, which, if followed by researchers, are supposed to lead to valid knowledge. These paths are drawn on maps based on assumptions about the nature of reality and the processes of human understanding. The map developed for Western science . during the past three centuries is based on the notion that reality consists of natural objects and that knowledge is a description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
671
0
22

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,017 publications
(699 citation statements)
references
References 5 publications
6
671
0
22
Order By: Relevance
“…In judging the optimum number of interviews, the researchers were guided by Polkinghorne (1989), Creswell (1998Creswell ( , 2007 and Kvale and Brinkmann (2009) who recommend that researchers interview between five and twenty five individuals who have all experienced the phenomenon, provided that they are long interviews. Moreover, Kvale and Brinkmann (2009) and Knox and Burkard (2009) suggest interviewing as many individuals as necessary to reach saturation, while Guest, Bunce and Johnson (2006) found that saturation occurs within the first twelve interviews, with basic elements for common themes being present as early as after six interviews.…”
Section: Stage 1: Approaches To Managing Place Brand Architecturesmentioning
confidence: 99%
“…In judging the optimum number of interviews, the researchers were guided by Polkinghorne (1989), Creswell (1998Creswell ( , 2007 and Kvale and Brinkmann (2009) who recommend that researchers interview between five and twenty five individuals who have all experienced the phenomenon, provided that they are long interviews. Moreover, Kvale and Brinkmann (2009) and Knox and Burkard (2009) suggest interviewing as many individuals as necessary to reach saturation, while Guest, Bunce and Johnson (2006) found that saturation occurs within the first twelve interviews, with basic elements for common themes being present as early as after six interviews.…”
Section: Stage 1: Approaches To Managing Place Brand Architecturesmentioning
confidence: 99%
“…A sample size of five to 25 participants is recommended for investigating shared experiences (21). We anticipated that 15-20 participants would be sufficient to meet sampling requirements for theoretical saturation (21)(22)(23).…”
Section: In-depth Interviewsmentioning
confidence: 99%
“…We anticipated that 15-20 participants would be sufficient to meet sampling requirements for theoretical saturation (21)(22)(23). Interviews were audio recorded, deidentified, and transcribed.…”
Section: In-depth Interviewsmentioning
confidence: 99%
“…Four of the participants self-identified as Hispanic, one as Lebanese, and one as White. Polkinghorne (1989) recommends a sample size of 5-25 participants for phenomenological inquiry. The recruitment of additional participants ceased once saturation of themes became evident.…”
Section: Participants and Study Proceduresmentioning
confidence: 99%